Validation Study of the Child and Youth Resilience Measure (CYRM-28) Among Dutch Youth - Jonkman, Harrie; Rooijen, Maaike van; Wiersma, Marte; Goor, Roel van (Frontiers in Psychiatry, 2022)
Purpose: This article reports on the examination of the psychometric properties of the 28-item Child and Youth Resilience Measure (CYRM-28) among a Dutch at risk sample. Methods: Descriptives, reliability tests, explorative as well as confirmative factor analysis and construct validity tests are set out on data collected of 525 at-risk youth (16-22 years) to identify factor structure, construct validity and consistency and reliability of the CYRM-28 in the Netherlands. Results: Our EFA didnot confirm but our CFA showed reasonable results for a three structure framework of the CYRM-28 (with individual, relational and contextual subscales). Overall results are similar to the results found in other international validation studies on measuring resilience among youngsters. The unclear findings individual and contextual subscales in the Dutch sample needs more research in the near future. Conclusion: Integral support of vulnerable youth needs to fit in with the lives and world of these youngsters in their transition to adulthood. Measuring resilience with the CYRM-28 can shine a light on this.